PENGARUH MEDIA POP-UP BOOK TERHADAP HASIL BELAJAR PPKN SISWA KELAS III DI SDN KESAMBI - Agustin, Lintang Dwi; Kurniawan, Machful Indra (Jurnal Pendidikan Dasar Flobamorata, 2024)
This study aims to determine the effect of Pop-Up Book Media on PPKn Learning Outcomes of Class III Students at SDN Kesambi, in terms of the learning outcomes of class III students in PPKN subjects, namely there are problems with low student learning outcomes in learning. The research population is 37 students. This research method uses a quantitative experiment, the type of Pre-Experiment research, assisted by SPSS 26 software. The results show that to test the hypothesis and answer the problem formulation, the data analysis technique uses a paired t-test. This can be seen from the average value when given the Pop-Up Book Media treatment on the PPKn Learning Outcomes of Class III Students at SDN Kesambi. After testing the hypothesis using the Paired T-Test t test, the average pretest data is smaller than the average posttest data. Sig value is obtained. (2-tailed) is less than 0.05 and the eta value is more than 0.14, meaning that using Pop-Up Book Media affects the PPKn Learning Outcomes of Class III Students at SDN Kesambi. This means that there is an increase in student learning outcomes after applying the use of Pop-Up Book Media to the PPKn Learning Outcomes of Class III Students at SDN Kesambi.